Physico-chemical characterization of caesium and strontium using fluorescent intensity of bacteria in a microfluidic platform. Issue 5 (1st May 2019) - Roh, Changhyun; Nguyen, Thi Toan; Shim, Jae-Jin; Kang, Chankyu
Abstract : Recently, the impact of radioactive caesium (Cs) and strontium (Sr) on human health and the ecosystem has been a major concern due to the use of nuclear energy. However, this study observed changes in green-fluorescent (GFP)-tagged Pseudomonas aeruginosa PAO1 biofilms by injecting non-radioactive caesium chloride (CsCl) and strontium chloride (SrCl2 ) into microstructures embedded in polydimethylsiloxane microfluidic devices, which were used due to their strong toxicity limitations. Four types of microstructures with two different diameters were used in the study. The change of biofilm thickness from fluid velocity and wall shear stress was estimated using computational fluid dynamics and observed throughout the experiment. The effect of pore space became a significant physical factor when the fluid was flowing through the microfluidic devices. As the pore space increased, the biofilm growth increased; therefore, triangular microstructures with the largest pore space showed the best growth of biofilm. Caesium chloride (CsCl) and strontium chloride (SrCl2 ), less toxic than radioactive caesium (Cs) and strontium (Sr), completely eradicated the P. aeruginosa PAO1 biofilm with low concentrations. The combined effect of toxicity, fluid velocity, wall shear stress and microstructures increased the efficiency of biofilm eradication. These findings on microfluidic chips can help to indirectly predict the impact on human public health and ecosystems without using radioactive chemicals.